Применение дескрипторов для сшивки изображений - Шевченко, Н. С. (ХНУРЕ, 2019)
The given work is devoted to the problem of image stitching. Image stitching is the process of matching, aligning and overlaying two or more images of a scene which is captured from different viewpoints. It is extensively used in numerous vision based applications. Image registration has five main stages: feature detection and description, feature matching, outlier rejection, derivation of transformation function, and image overlaying. Timing and accuracy of feature-based image stitching mainly depend on computational efficiency and robustness of the selected descriptor. In this work, SURF and SIFT descriptors were considered. For experimental research, the language of JAVA and OpenCV library were used.